Proyecto de construcción de una variante en el trazo original (Vía de Evitamiento) - Águila Panduro, Rubén Del (1995)
From h < 1ce many < ~ us there was need to build a < ~ vi < 1 that avoids the p < tso vehicles of < tito tonnage through the Centre of the cities of Tarapoto, Morales and the Banda de Shilcayo, due to the growth of tninsito that has been developed in the course of the last dec < ad, is Llsi than hllce approx. < tdamente JO years the INADUR create a project via avoidance I was born < t in the city of Morales specifically at the junction of the Salcweny-Tupac Amant shreds, par < ~ finaliz < ~ r at 656 km of the marginal highway of the southern forest, in areas corresponding to the Bllmla de Shilcayo district. The present work of T_ ~ _sis ~ terminates the proble ~ matica that currently comes causing is of the crossing of this stroke original by land tiel Campus University, as well as of the step of this via by areas of high density poblacioillll with that llhorel is cuentll due lll great desllrrollo urban that comes noticing is. For this reason is plllntelln three possible nttlls...